Teddy Guardian / Siti Nur Huwaini Hadzri … [et al.] - Hadzri, Siti Nur Huwaini; Omar Zuki, Nur Syahira; Mohd Nazri, Nur Qistina Batrisyia; Muhamad Fadzli, Mashitah; Mohamad Roseli, Nur Hazwani (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Violent crime ruined some communities' lives, especially to children, special - need kids, young adults and women. Consequently, some victim that affected by crime is highly potential to suffer from physical injury and psychological harm like traumatic disorder, identity disorder, anxiety, depression, bipolar, impaired memory, sense of helplessness, guilt and much more.This is due to the fact that there are several causes of this violent crime such as genetic predisposition, neurochemical abnormalities, and abuse or neglect experience. Some cases like hostage issues will lead to “stockholm syndrome” which causes the victim to have positive feelings towards their kidnapper over time. Therefore, this syndrome will reduce the victim’s sense of danger. In order to address this issue, we designed a Teddy Guardian as a safety device in providing warning alarms to users when any possible violent outcome appears. Besides, this security device is equipped with GPS and camera that links to the Teddy Guardian customized application (apps). The novelty of this Teddy Guardian is the animal shape of a bear, a symbol of defense for the weak communities like children and women. As technological advancement, Teddy Guardian vision is to aid these communities to defend themselves effectively during emergencies. This smart device also comes with an affordable price, RM179 in which all types of social class can afford to have one. Moreover, this innovative product will be notable as a universal self-defense device in 2024 - 2025, meeting the industrial demand towards security purposes.